The expression of the Cuphea palustris thioesterase CpFatB2 in Yarrowia lipolytica triggers oleic acid accumulation. (27th November 2015) - Stefan, Alessandra; Hochkoeppler, Alejandro; Ugolini, Luisa; Lazzeri, Luca; Conte, Emanuele
Abstract : The conversion of industrial by‐products into high‐value added compounds is a challenging issue. Crude glycerol, a by‐product of the biodiesel production chain, could represent an alternative carbon source for the cultivation of oleaginous yeasts. Here, we developed five minimal synthetic glycerol‐based media, with different C / N ratios, and we analyzed the production of biomass and fatty acids by Yarrowia lipolytica Po1g strain. We identified two media at the expense of which Y. lipolytica was able to accumulate ∼5 g L −1 of biomass and 0.8 g L −1 of fatty acids (0.16 g of fatty acids per g of dry weight). These optimized media contained 0.5 g L −1 of urea or ammonium sulfate and 20 g L −1 of glycerol, and were devoid of yeast extract. Moreover, Y. lipolytica was engineered by inserting the FatB2 gene, coding for the CpFatB2 thioesterase from Cuphea palustris, in order to modify the fatty acid composition towards the accumulation of medium‐chain fatty acids. Contrary to the expected, the expression of the heterologous gene increased the production of oleic acid, and concomitantly decreased the level of saturated fatty acids. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 32:26–35, 2016